Research on In-situ Sludge Solidification in the Ecological Refuse Landfill Closure Project - ZHANG Xiaoyu; ZHOU Xianjin; CAO Jun (Renmin Zhujiang)
For the site pilot test of in-situ sludge solidification in a large ecological landfill closure project in southwest China,this paper adopts five kinds of curing agent mix ratios for site construction,adds curing agent and conducts in-situ mixing with cleaning and mixing equipment after pretreatment of sludge,and drills and samples the treated refuse soil after rolling and curing.The test results show that the sludge treated with five kinds of curing agents could meet the design requirements on pH,moisture content,shear strength and unconfined compressive strength.Through the comparison of shear strength and unconfined compressive strength,the effect of No.5 curing agent is the best,that is,in the curing agent,the ordinary silicate content is 19.3%,the fly ash content is 6.43%,and the curing agent ratio is 25.73%.In the actual construction,the No.5 mix ratio is widely used.In addition,according to the difference of physical properties of sludge in level and treatment direction,the mix ratio of curing agent and the parameters of mixing equipment shall be adjusted appropriately to ensure the uniformity of sludge curing effect.